2018
DOI: 10.3168/jds.2018-14648
|View full text |Cite
|
Sign up to set email alerts
|

Milk replacer restriction during early life impairs the live body weight and progesterone patterns of ewe lambs during the replacement period

Abstract: Nutritional programming caused by feed restriction during the early life may counteract the profitability of the dairy sheep farm. However, most studies have been focused exclusively on the prenatal period, and scarce information regarding the effect of milk replacer (MR) restriction on feed efficiency [residual feed intake (RFI)] and progesterone patterns of replacement ewe lambs is available. Therefore, in the present study 40 Assaf female newborn lambs were penned individually and assigned randomly to 1 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
(46 reference statements)
4
16
1
Order By: Relevance
“…The impact of early-life stress on the brain's capability to produce neurosteroids such as progesterone has been studied previously. In this regard, evidence demonstrated that experiencing early life stress could reduce the level of neurostroids in the brain (Brunton 2015;Santos et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of early-life stress on the brain's capability to produce neurosteroids such as progesterone has been studied previously. In this regard, evidence demonstrated that experiencing early life stress could reduce the level of neurostroids in the brain (Brunton 2015;Santos et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding lambs, several studies have shown that metabolic programming events are caused by early feed restriction (Davies and Owen, 1967;Greenwood et al, 2004;Galvani et al, 2014), with negative long-term effects after the period of feed restriction. In this sense, previous studies have demonstrated negative consequences not only on the health status (Frutos et al, 2018) and feed efficiency traits (Santos et al, 2018c,d), but also on the onset of puberty in replacement ewes lambs (Santos et al, 2018c). However, even though we have found several studies in children (Ruchat et al, 2014), cattle (Soberon et al, 2012;Soberon and Van Amburgh, 2013;Alexandre et al, 2015), and pigs (Vincent et al, 2015), to our knowledge no studies have described the effects of early feed restriction at the gene expression level in artificially reared female Assaf lambs.…”
Section: Introductionmentioning
confidence: 68%
“…For this purpose, 4 liver samples from each group (8 lambs in total) were selected to cover the complete range of values of live BW at slaughter in each group and to avoid differences in birth weight between groups. Accumulated MR intake and animal performance of these preweaning lambs selected for omics (8 preweaning lambs in total) are summarized in Table 2 and Figure 1, whereas the rest of parameters measured at slaughter (16 preweaning lambs in total) are described in Santos et al (2018c). The nonslaughtered animals (24 lambs in total) were weaned and fed ad libitum a TMR to study the effects of metabolic programming provoked by early feed restriction during the replacement phase (Frutos et al, 2018;Santos et al, 2018c).…”
Section: Animal Diets and Samplingmentioning
confidence: 99%
“…Regarding ruminants, a previous study (Frutos et al, 2018) B cells or non-immune cells] was observed in RES lambs, which has been suggested as a mechanism implemented to keep the homeostasis at intestinal level (Zhang and Ghosh, 2002;Malmuthuge et al, 2012;Villena et al, 2014). In any case, all these alterations in the gut could be, at least, partially responsible for the reduced animal performance of RES lambs.…”
Section: Discussionmentioning
confidence: 91%
“…It must be considered that GGT enables the metabolism of antioxidants, inflammatory molecules, drug metabolites, glutathione and glutathionylated xenobiotics (Koenig and Seneff, 2015). Therefore, the lower levels of GGT observed in the RES ewe lambs along the whole experimental period might be associated to several indicators of intracellular stress and inflammatory response (e.g., phosphatidylserine compounds and prostaglandin E2-biotin) that were over accumulated in the plasma of these animals according to their metabolome profile published previously elsewhere (Santos et al, 2018).Moreover, other studies have shown that malnutrition is related to oxidative stress conditions as a consequence of chronic inflammation events (Ece et al, 2007). In the present study a transitory imbalance in the antioxidant status during the suckling period could be observed in the pre-weaned RES lambs (e.g., lower FRAP and PON values), which also manifested proinflammatory conditions at ileal level.…”
Section: Discussionmentioning
confidence: 92%